FinTech, financial inclusion, and different dimensions of inequality: channels and evidence - Figueira, Catarina; Subramanian, Lakshmy (British Academy of Management, 2023)
This study investigates the relationship between FinTech, financial inclusion, and different dimensions of inequality, (gender, income, and carbon) for a panel of 113 nations using the Global Findex waves of survey data from 2011, 2014, 2017, and 2021. The study employs structural equation modelling to simulate both the direct and indirect effects. The key findings include (i) FinTech significantly increases income inequality and reduces gender inequality (through financial inclusion). (ii) FinTech promotes financial inclusion. (iii) Financial inclusion reduces all dimensions of inequality. (iv) Regulatory quality, education, and access to credit reduce different dimensions of inequality through financial inclusion. These results add to a modest but growing body of work on the role of FinTech and financial inclusion in fostering better resource distribution and inclusive development across countries. Moreover, this is the first study to investigate different dimensions of inequality and model interrelationships. The study provides preliminary evidence of the varying distributional effects of FinTech and financial inclusion on different dimensions of inequality.
Keywords: Financial Management Track; Financial Technology (FinTech); Financial Intermediation